Agronomy Climate Change & Food Security (IntechOpen, 2020)
Climate change is a serious threat to field crop production and food security. It has negative effects on food, water, and energy security due to change in weather patterns and extreme events such as floods, droughts, and heat waves, all of which reduce crop productivity. Over six chapters, this book presents a comprehensive picture of the importance of agronomy as it relates to the United Nations' Sustainable Development Goals. With an emphasis on the goals of Zero Hunger and Climate Change, this volume examines sustainable agronomic practices to increase crop productivity and improve environmental health.